Receptor subtype abundance as a tool for effective intracellular signalling - Myslivecek, Jaromír; Nováková, Martina; Klein, Martin (Cardiovascular & hematological disorders drug targets, 2008)
The regulation of heart function is one of the essentials for the survival of organism. Therefore, the effective mechanisms of regulation can minimize the energy requirements and improve the ability to react to different needs on time and appropriately. Two receptor types, beta-adrenoceptors and muscarinic receptors, with almost antagonistic function, are "basic regulators" of the heart parameters. It is relevant to mention that beside the main adrenoceptors and muscarinic receptors subtypes (beta(1)- and M(2)-subtype), other minor subtypes that regulate heart function, i.e. beta-, beta-adrenoceptors, alpha(1)-adrenoceptors and minor subtypes of muscarinic receptors (M(1), M(3) and M(5)) are present in the heart. In this regard is intriguing that just two catecholamines (adrenaline, noradrenaline) have many "targets"--receptors that differ so much in the functional consequences of their activation: while beta(1)- and beta(2)-adrenoceptors cause cardiostimulation, beta(3)-adrenoceptors are responsible for cardioinhibition and alpha(1)-adrenoceptors contribute to enhanced inotropy. Similarly, some data show that other muscarinic receptors than M(2) muscarinic subtype, are expressed in the heart and these minor subtype(s) can contribute to the heart regulation in similar way as beta(3)-adrenoceptors to the catecholamine action. Taken together, regulation of heart function through different receptor subtypes and using homologous and heterologous regulation can represent an effective tool for coping with permanently changing environmental conditions.
Keywords: biologické modely; Heart; Models, Biological; Receptors, G-Protein-Coupled; Receptors, Muscarinic; signální transdukce; receptory muskarinové; receptory spřažené s G-proteiny; Animals; Signal Transduction; zvířata; Humans; srdce; lidé; Receptors, Adrenergic, beta; beta-adrenergní receptory